MANAJEMEN DISIPLIN KINERJA GURU PASCA MUTASI - Fathur Rahman (Manajer Pendididikan, 2015)
The purpose of this study in general to describe the discipline teacher performance post mutations in Senior High School 1 Lubuklinggau. Data were collected by interview, observationand dokumentation technique. To analyze data, this study uses two steps; 1) inductive descriptive qualitative and 2) presentation analysis. Analysis of the data in this study consists of four interacting components as follows: (1) data collection; (2) reduction of data; (3) the presentation of data (display) data as well; (4) verification and conclusion. Conclusion that labor discipline management post mutations in Senior High School 1 Lubuklinggau an increase in discipline teacher performance.Keyword: management, disciplined performance, teachers, mutation